2016
DOI: 10.1080/17474086.2016.1182858
|View full text |Cite
|
Sign up to set email alerts
|

Double hit lymphoma: from biology to therapeutic implications

Abstract: So-called 'double-hit lymphomas' (DHL) or 'triple hit lymphomas' (THL) occur when MYC is concurrently rearranged with BCL2 and/or BCL6. These tumors are characterized by high proliferation rate and a very poor outcome following standard R-CHOP (rituximab, cyclophosphamide, doxorubicin vincristine and prednisone) therapy, in most (though not all) studies that have looked at this. Though there is a paucity of published experience with other chemotherapy regimens, there is emerging evidence that more intensive ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 79 publications
0
23
0
Order By: Relevance
“…It provides B-cells with simultaneous suppression of checkpoints through BCL6 along with the pro-growth and survival effects of MYC and BCL6. Not surprisingly the combination of MYC and/or BCL2 with BCL6 in DLBCL has been linked to unfavorable clinical outcomes (12). …”
Section: Introductionmentioning
confidence: 99%
“…It provides B-cells with simultaneous suppression of checkpoints through BCL6 along with the pro-growth and survival effects of MYC and BCL6. Not surprisingly the combination of MYC and/or BCL2 with BCL6 in DLBCL has been linked to unfavorable clinical outcomes (12). …”
Section: Introductionmentioning
confidence: 99%
“…4,5 Concurrent derangements of BCL2 (an anti-apoptotic actor) and BCL6 (a transcription repressor) can be either the "second-hit" or "third-hit" in these disease states. 1 These lymphomas were described as epidemiologically infrequent with most patients being adults who presented with widespread and often extranodal disease.…”
Section: R Esu L Tsmentioning
confidence: 99%
“…However, a histopathological study of 492 mature aggressive B-cell neoplasms concluded that the proliferation fraction by Ki67 immunostaining is not useful to prescreen B-cell lymphomas as DHL or THL [89]. DEL overexpress Myc and BCL2/BCL6 but typically without rearrangements of these genes [24,87], though cut-off of double expression is not universally defined so far. THL is associated with rearrangement of Myc, BCL2 and also BCL6 [24].…”
Section: High Risk Dlbclmentioning
confidence: 99%
“…DHLs are seen in approximately 5-10% of DLBCL patients and usually involve rearrangement of Myc oncogene with BCL2 (or sometimes BCL6) protein [24,86,87]. Using immunophenotypical data from larger studies on DHL, Aukema et al found that coexpression of CD10, BCL6, BCL2, and a high Ki67 proliferation index might be used to select potential DHLs in morphologically diagnosed DLBCL, though it may not be specific [88].…”
Section: High Risk Dlbclmentioning
confidence: 99%